Policing across borders: Line of Duty and the politics of national identity. Issue 2 (1st October 2014) - Joy, Stuart
In this article, I argue that the first series of Line of Duty (2012–) invites viewers to consider the wider politicized function of the police as well as depictions of criminality in Britain. I describe how the series reflects a broader shift in the understanding of the British crime drama as not simply a reproduction of national concerns, but in relation to new discourses of transnational anxiety. I analyse how representations of crime and criminality are viewed through the lens of current news media trends to examine the relationship between the British crime drama and the wider socio-economic and political concerns in which articulations of both national and increasingly transnational identities can become visible.